Unsuccessful Conquest and Successful Subordination. A Contribution to the Theory of Intersocial Relations - Brzechczyn, Krzysztof (Rodopi, 1993)
The aim of this paper is to extend the Leszek Nowak's theory of socialist empire by introducing weaker forms of intersocial relation, e. gr. unsuccessful attempt at conquest and subordination. In the light of concretization of the model of socialist empire some facts from history of Soviet Union (intervention of the Entente and World War II) and socialist countries (autonomy of Albania and Romania in socialist bloc) are explained.
Keywords: Non-Marxian historical materialism; Soviet Union; Empire; Socialism; Communism; Socialist bloc